Development of Children’s Talent and Creativity through Digital Media - Siti Eni Aisyah Simbolon (Maharot : Journal of Islamic Education, 2022)
Inappropriate use of smartphones can have a negative impact on children's development so it is necessary to utilize smartphones in developing children's talents and creativity. This article aims to find out alternative strategies for developing children's talents and creativity through digital media. This research is library research. Data collection is done by documentation technique. The sources of research data were obtained from articles, journals related to the problem being studied which were obtained from internet sites. The results of this study are alternative strategies in developing children's talents and creativity using smartphones during a pandemic can be done with expressions of love for the Qur'an, exploration of the yard, creating art at home, and creating caring. Efforts to develop children's talents and creativity can be done by creating a fun playing environment.